Influências do brown carbon e black carbon na forçante radiativa dos aerossóis no Pantanal mato-grossense - Raymundo, Kelly Sousa Romera (2023)
Aerosols have a significant effect on Earth's climate. They affect the amount of solar radiation reaching the Earth's surface and have a direct impact on global warming. One of the major sources of uncertainties associated with aerosol impact on climate is related to the light-absorbing fraction that is not black carbon (BC), known as brown carbon (BrC). In this study, BC and BrC were characterized and quantified to estimate their effects on total absorption. The radiative forcings of these two components were also calculated for the surface and the top of the atmosphere, as well as for BC and BrC fractions. The average values obtained for the scattering coefficient () at 525 nm were 6.16±5.75 and 54.51±81.53 Mm-1 for the rainy and dry periods, respectively. For the absorption coefficient () at 590 nm, the averages were 0.52±0.49 and 3.64±4.21 Mm-1 during the rainy and dry periods, respectively. Analysis of aerosol optical properties revealed the seasonal behavior of aerosol particles, which were more abundant in the dry period due to local and regional biomass burning. Regarding BC concentration, the Pantanal region showed average values 55% higher than the results obtained by Artaxo et al. (2013) for the ZF2 site (2008-2012) during the dry period and only 15% higher during the rainy period. The percentage of BrC in total absorption was approximately 10% and 24% for the dry and rainy periods at 470 nm, respectively. In Rio Branco, Ponczed et al., 2022 estimated that BrC accounted for approximately 20% of total absorption at 470 nm, while at the ATTO site, it was approximately 24% at 370 nm (SATURNO et al., 2018). The diurnal variations of the absorption coefficient, scattering coefficient, and single scattering albedo ( 0 ) were not pronounced and were dominated by the boundary layer dynamics. The angstrom absorption exponent () for the spectral ranges of 370-590 nm and 370-880 nm were higher during the dry period, indicating a possible increase in fine particle concentration emitted from biomass burning. The angstrom absorption exponent for 370-590 nm showed strong contributions from BrC and exhibited similar behavior between the dry and rainy periods, with an approximate 10% difference due to BC emissions. The top-of-atmosphere radiative forcing (FR) had averages of -0.89±0.66 and -0.42±0.05 Wm-2 for the dry and rainy seasons, respectively, while at the surface, the FR averages were -6.80±2.17 and -5.23±0.17 Wm-2 , respectively. The contribution of BC to top-of-atmosphere heating is nearly 60% greater compared to BrC during the dry period. Concerning FR values, Procópio (2005) estimated variations from -26 to - 62 Wm-2 at the surface in an Amazon-Cerrado transition region. Meanwhile, Palácios et al. (2015) estimated values ranging from 10 to -63 Wm-2 for the Pantanal-Cerrado transition region. In this study, the FR values at the surface ranged from -5 to -17 Wm2 . This study provided unprecedented results for the region and can contribute to a better understanding of the energy balance in the Pantanal as well as more accurate estimations of aerosol contributions in climate change models.